Common dolphin Delphinus delphis occurrence off the Wild Coast of South Africa. Issue 4 (1st October 2020) - Caputo, M; Froneman, PW; Plön, S
Abstract : Despite their typical large group sizes, limited research exists on the occurrence of common dolphins Delphinus delphis because of the pelagic, offshore nature of this species and the lack of barriers to their movement in this environment. The main purpose of our study was to investigate the occurrence of common dolphins off the Wild Coast of South Africa (western Indian Ocean) and whether spatiotemporal and environmental conditions affected their encounter rate, relative abundance and mean group size. The annual sardine run in this region, during austral winter (May to July), is considered a main driver of dolphin occurrence; however, our boat-based surveys over the period 2014–2016 indicated that common dolphins occur and feed in this area outside of this time-frame. In terms of environmental factors, the largest group (∼1 250 animals) was found in the deepest waters. Additionally, at Hluleka, dolphins were observed primarily feeding, which could suggest that this coastal area is highly productive. As common dolphin distribution is thought to be correlated with prey distribution, our findings suggest that sufficient prey exists along the Wild Coast both during and outside the annual sardine run to sustain large groups of the dolphins and that their presence in the area is not solely a function of the sardine run.